Comparative Analysis of Representation of the State Campaign: How Vremya and KazPravda frame the “People’s IPO”. (Herald of Journalism, 2016)
Using framing theory and framing matrix approach the authors examined coverage of the “People’s IPO” in Kazakhstan. This research revealed that the same issue might be covered in completely distinct ways: only Be Careful! frame was mutual for both newspapers out of 13 frames. Despite the fact that more than 70% of quotes belong to “State” and “Issuer” source categories, meanings of articles completely differ.
Keywords: frames; framing theory; newspapers; People’s IPO; news sources